2015
DOI: 10.1037/hea0000155
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counselors’ implicit racial attitudes and their relationship to communication.

Abstract: Objective Implicit racial attitudes are thought to shape interpersonal interactions and may contribute to health care disparities. This study explored the relationship between genetic counselors’ implicit racial attitudes and their communication during simulated genetic counseling sessions. Methods A nationally representative sample of genetic counselors completed a web-based survey that included the Race Implicit Association Test (IAT). A subset of these counselors (n=67) had participated in an earlier stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 46 publications
(88 reference statements)
3
53
1
Order By: Relevance
“…Consistent with other populations, health care providers demonstrate implicit biases indicative of more negative attitudes toward African Americans than Whites (Blair et al, 2013a; Cooper et al, 2012; Green et al, 2007; Haider et al, 2011, 2015a, 2015b; Hausmann et al, 2015; Oliver, Wells, Joy-Gaba, Hawkins, & Nosek, 2014; Sabin, Nosek, Greenwald, & Rivara, 2009; Schaa, Roter, Biesecker, Cooper, & Erby, 2015; Stepanikova, 2012; for null effects, see Penner et al, 2010; Sabin, Rivara, & Greenwald, 2008), more negative attitudes toward Latinos than Whites (Blair et al, 2013a, 2013b; Stepanikova, 2012), and somewhat more negative attitudes toward Native Americans than Whites (Sabin, Moore, Noonan, Lallemand, & Buchwald, 2015). Health care providers also exhibit negative implicit biases against overweight/obese individuals (Phelan et al, 2014; Sabin, Marini, & Nosek, 2012; Teachman & Brownell, 2001; Waller, Lampman, & Lupfer-Johnson, 2012), gay and lesbian people (Burke et al, 2015; Sabin, Riskind, Nosek, 2015), lower social class (Haider et al, 2011, 2015a, 2015b), injecting drug users (von Hippel, Brener, & von Hippel, 2008), and wheelchair users with spinal cord injuries (Galli, Lenggenhager, Scivoletto, Molinari, & Pazzagila, 2015).…”
Section: Direct Evidence Of Biased Attitudes and Stereotypes Among Hesupporting
confidence: 54%
“…Consistent with other populations, health care providers demonstrate implicit biases indicative of more negative attitudes toward African Americans than Whites (Blair et al, 2013a; Cooper et al, 2012; Green et al, 2007; Haider et al, 2011, 2015a, 2015b; Hausmann et al, 2015; Oliver, Wells, Joy-Gaba, Hawkins, & Nosek, 2014; Sabin, Nosek, Greenwald, & Rivara, 2009; Schaa, Roter, Biesecker, Cooper, & Erby, 2015; Stepanikova, 2012; for null effects, see Penner et al, 2010; Sabin, Rivara, & Greenwald, 2008), more negative attitudes toward Latinos than Whites (Blair et al, 2013a, 2013b; Stepanikova, 2012), and somewhat more negative attitudes toward Native Americans than Whites (Sabin, Moore, Noonan, Lallemand, & Buchwald, 2015). Health care providers also exhibit negative implicit biases against overweight/obese individuals (Phelan et al, 2014; Sabin, Marini, & Nosek, 2012; Teachman & Brownell, 2001; Waller, Lampman, & Lupfer-Johnson, 2012), gay and lesbian people (Burke et al, 2015; Sabin, Riskind, Nosek, 2015), lower social class (Haider et al, 2011, 2015a, 2015b), injecting drug users (von Hippel, Brener, & von Hippel, 2008), and wheelchair users with spinal cord injuries (Galli, Lenggenhager, Scivoletto, Molinari, & Pazzagila, 2015).…”
Section: Direct Evidence Of Biased Attitudes and Stereotypes Among Hesupporting
confidence: 54%
“…It is also conceivable that the genetic counselors had more difficulty interpreting non-verbal cues from minority clients, as has been reported in other settings (Levine & Ambady, 2013). Conversely, delivery by telephone may reduce differences in underlying implicit biases by genetic counselors (Schaa, Roter, Biesecker, Cooper, & Erby, 2015), the occurrence of which has been reported in other medical settings (Blair et al, 2013; Cooper et al, 2012). Of note, however, non-Hispanic white participants reported overall higher satisfaction than minority participants.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic counselors are charged with delivering effective communication regardless of patients’ beliefs or backgrounds, and creating a diverse workforce could increase training opportunities for growth in cultural competency that would benefit patient care. A 2015 study recruited genetic counselors to take the Race Implicit Association Test, following which a small group of those counselors were video‐recorded in simulated prenatal and cancer consultations with minority patients (Schaa, Roter, Biesecker, Cooper, & Erby, 2015). The study found that the majority of counselors showed moderate‐to‐strong ‘pro‐White’ implicit bias.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the majority of counselors showed moderate-to-strong 'pro-White' implicit bias. The subset of individuals with 'stronger pro-White bias' were rated as displaying lower positive affect and using less emotionally responsive communication when counseling minorities (Schaa et al, 2015). In order to more effectively care for an increasingly diverse patient population, bor-intensive programs that involve funding from the initiating school, along with educational opportunities and faculty or professional mentorship (Brown & Marshall, 2008;Murray et al, 2016).…”
mentioning
confidence: 99%